Metal base for maxillary complete denture - Baso, Maharani K.; Ikbal, Muhammad; Dammar, Irfan; Mude, Acing H. (Hasanuddin University, 2020)
Objective: A successful denture should have dimensional stability in order to enhance chewing efficiency, increase patient’s comfort, and prevent injury to the oral tissue. However, fracture of acrylic denture base is occasionally an avoidable complication because the mechanical properties of acrylic resin may not be sufficient to withstand masticatory stress. This case report describes the step-by-step fabrication of a maxillary metal based complete dentureMethods: A 58-year-old female patient arrived at Dental Hospital Hasanuddin University with complaints of impaired appearance and difficulty chewing due to the loss of all maxillary and mandibular teeth. Previously, the patient had worn dentures twice. First, in 2012 using full maxillary dentures for 3 years. Second, in 2016 there were more dentures full of maxillary and mandibular prostheses because the denture before were broken. But, the dentures are rarely used because they are loose. The patient feels uncomfortable and wants to make dentures. The treatment stage: clinical and radiographic examination, preliminary and finally impression, manufacturing of maxillary metal bases, manufacturing of bite rim, determination of vertical dimensions, arranging the artificial teeth, try-in denture, insertion and control.Results: The treatment is the manufacture of a maxillary acrylic complete denture with a metal framework base and a acrylic complete denture for the mandibular, gived more comfortable and retentive.Conclusion: Metal bases for complete dentures has been used successfully and provide many advantages over the more commonly used acrylic resin. With metal bases in dentures, the patient benefits by having a more comfortable, better fitting and stronger prosthesis.